PENGEMBANGAN MULTIMEDIA INTERAKTIF DALAM PEMBELAJARAN GEOMETRI UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI CALON GURU SEKOLAH DASAR - Fitriani, Andhin Dyas (Prodi Teknologi Pendidikan, 2014)
Abstract. Communication is an essential part of mathematics and mathematics education. Communication is also a way to share ideas and classify understanding. Geometry in elementary school (SD) on the one hand is a very strategic mathematics study to encourage mathematics learning towards appreciation and experience of learning by making the learning meaningful. Van Hiele suggests that there are three main elements in the teaching of geometry, namely time, teaching materials, and teaching methods applied. One of the things that hinder a student's geometric thinking skills is the teaching methods employed by teachers in the classroom. The role of teachers in the 21st century includes